2022
DOI: 10.1111/tpj.15691
|View full text |Cite
|
Sign up to set email alerts
|

Translational profile of developing phellem cells in Arabidopsis thaliana roots

Abstract: The phellem is a specialized boundary tissue providing the first line of defense against abiotic and biotic stresses in organs undergoing secondary growth. Phellem cells undergo several differentiation steps, which include cell wall suberization, cell expansion, and programmed cell death. Yet, the molecular players acting particularly in phellem cell differentiation remain poorly described, particularly in the widely used model plant Arabidopsis thaliana. Using specific marker lines we followed the onset and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Combination of heat and osmotic stress (H+O) was imposed to Arabidopsis plants at 8 DAG, on the onset of root secondary development [ 31 ]. In order to evaluate the effect of combined stress on root suberization, we performed a morphological and spatio-temporal characterization of root suberization, targeting the expression of the suberin biosynthesis marker Glycerol-3-phosphate acyltransferase 5-GPAT5 (pGPAT5:mCITRINE-SYP122 [ 30 ], as well as cell-wall suberization, using FY staining [ 36 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Combination of heat and osmotic stress (H+O) was imposed to Arabidopsis plants at 8 DAG, on the onset of root secondary development [ 31 ]. In order to evaluate the effect of combined stress on root suberization, we performed a morphological and spatio-temporal characterization of root suberization, targeting the expression of the suberin biosynthesis marker Glycerol-3-phosphate acyltransferase 5-GPAT5 (pGPAT5:mCITRINE-SYP122 [ 30 ], as well as cell-wall suberization, using FY staining [ 36 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we used 8 DAG Arabidopsis to study the influence of a combination of heat and osmotic stress on root suberization. At 8 DAG, Arabidopsis root system is already complex, with secondary development present in a small portion of the upper part of the main root, with suberized phellem as the outermost layer [ 31 ], and below this region, in primary development, the main root has a layer of suberized endodermis around the stele. In addition, LRs are already present, showing equivalent morphology of younger roots, both undergoing primary development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Lopes et al, (2019) identified CYP82D , CYP76A and CYP705A in phellogen samples. When Arabidopsis root phellem was studied for suberin synthesis, it was possible to detect the expression of suberin synthesis components; CYP86A1 , CYP86B1 , FAR1/4/5 , GTPAT5/7 , FACT , and ASFT [ 74 ] indicating a conservative mechanism for suberin biosynthesis.…”
Section: Molecular Basis Of Cork Developmentmentioning
confidence: 99%